Students’ migration in a Portuguese hinterland public university - Fonseca, M.; Justino, E.; Amaral, A. (Studies in Higher Education, 2020)
Several studies on the access to public higher education in Portugal have analysed the students’ migration flows. Those studies, in general, do not consider the micro-level migration decisions of students. This study analyses the students’ migration flows by fields of study or programmes, grades, social background and region of origin for a small Portuguese public university located in the hinterland, in a second-tier city. Local candidates with higher grades, tend to leave and enrol outside in a larger city. This migration flow induces a social downgrading in the region of origin. There are however counter flows of students coming from the outside to the region and that is why the university accommodates a very large segment of mobile students; this can have a high potential for the university and the city as attracting students from all over the country may change the social environment and create innovation.